Racism in metropolitan areas - Pinxten, Rik; Preckler, Ellen (Culture and politics/politics and culture, 2005)
For several decades, a political discourse, which incites exclusion and hatred againt those who are perceived as different, has been gaining ground, most notably in affluent and developed countries. Focusing on the growth of racism in large cities and urban areas, this volume presents the views of international scholars who work in the social sciences and statements by non-practicing academics such as journalists and policy makers. The contributions of the scientists and the non-academic specialists are grouped around common themes, highlighting existing debates and bringing together widely s.